Partnering for success: the case of UEM Group Berhad in Saudi Arabia / Mohd Saleh Mohamed Bamadhaj - Mohamed Bamadhaj, Mohd Saleh (Faculty of Business and Management, 2009)
Partnership between local and foreign businesses has become the most common method in the business world today in believing for the expansion of business and creates strong relationship between nations for achieving mutual benefit by making the business operation easier in foreign country. Partnership represents the most important component in expanding business overseas in order to ease the operations abroad. UEM has expected that by partnering with the local party in Saudi Arabia can determine these successes in partnering in foreign country. However, there are obstacles in partnering with the Saudi party. Amongst the barriers are different cultural and management style, communication barriers and involvement of other partners in the partnership. These problems have created great challenges to UEM Group for gaining success in investing into Saudi Arabia. In order to establish success in Saudi Arabia, UEM has adopted new strategies to maintain its strong relationship with Saudi Arabia’s partners. The strategies that UEM has executed were setting up a representative office in Saudi Arabia, improve communication skills, and establish a stronger relationship with the local parties and the successor of the owner in Saudi Arabia. Leveraging the government to ensure a strong government to government relationship between Malaysia and Saudi Arabia was one of UEM’s agenda to support the partnership. The strategies UEM can adopt is to ensure a better development for the partnership is to developed the communication skills, learn more deep into their culture and understanding to ensure a better partnership in the future.